Visual inferences of material changes: color as clue and distraction - Zaidi, Qasim (2011)
In a snapshot, a scene consists of things, but across time, the world consists of processes. Some are cyclical, for example, trees changing foliage through the seasons, surfaces getting wet and drying out; others are unidirectional, for example, fruit ripening and then decaying, or dust accumulating on surfaces. Chemical and physical properties of objects provide them with specific surface patterns of colors and textures. When endogenous and exogenous forces alter these colors and textures over time, the ability to identify these changes from appearances can have great utility in judging the composition, state, and history of objects. This short review presents thoughts on studying visual inferences of the properties of materials and their changes, including how to acquire calibrated images of time-varying materials, how to model time-varying appearance changes, how to measure observers’ identification abilities, and how to parse out the perceptual qualities that help or hinder in recognizing materials and their states. For instance, if color information is removed, observers do significantly worse at recognizing materials and their changes, especially for organic materials. The role of color in object and scene recognition is still being debated, so elucidating color’s role in material identification may also help to resolve the wider issue. This review introduces material change as an object of study in human perception and cognition, because the visual traces of changes are integral components of material and object identity. Visually based judgments of materials share the property of propensity with mental inferences, and conscious or unconscious visual imagery may play a role in setting expectancies for object shapes and properties.